Conjunctival cytology in patients treated for ocular infectious diseases - Sh. A. Dzhamalova; N. R. Yangieva; Z. Kh. Kuryazova (Journal of Ophthalmology, 2021)
Background: Anti-inflammatory therapy is a mainstay of treatment for patients with ocular inflammatory disorders. Although glucocorticosteroids (GCS) demonstrate a potent anti-inflammatory and anti-allergic effect, treatment with GCS is associated with a risk of serious side effects. Non-steroidal anti-inflammatory agents (NSAIDs) possess somewhat lower anti-inflammatory activity compared to GCS, and their development and incorporation into clinical eye care practice seem reasonable.